2023
DOI: 10.3389/fmed.2023.1292056
|View full text |Cite
|
Sign up to set email alerts
|

Hyperangulated blades or direct epiglottis lifting to optimize glottis visualization in difficult Macintosh videolaryngoscopy: a non-inferiority analysis of a prospective observational study

Viktor A. Wünsch,
Vera Köhl,
Philipp Breitfeld
et al.

Abstract: PurposeIt is unknown if direct epiglottis lifting or conversion to hyperangulated videolaryngoscopes, or even direct epiglottis lifting with hyperangulated videolaryngoscopes, may optimize glottis visualization in situations where Macintosh videolaryngoscopy turns out to be more difficult than expected. This study aims to determine if the percentage of glottic opening (POGO) improvement achieved by direct epiglottis lifting is non-inferior to the one accomplished by a conversion to hyperangulated videolaryngos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Our findings show that better glottic view with hyperangulated videolaryngoscopy did translate into reduced tracheal intubation time, with higher success rates when used in patients with predicted difficult airways by experienced anaesthetists. Previous study findings [10], as well as the findings of our subgroup analysis show that the highest improvement in POGO occurred when hyperangulated videolaryngoscopy was used to rescue failed Macintosh videolaryngoscopy.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Our findings show that better glottic view with hyperangulated videolaryngoscopy did translate into reduced tracheal intubation time, with higher success rates when used in patients with predicted difficult airways by experienced anaesthetists. Previous study findings [10], as well as the findings of our subgroup analysis show that the highest improvement in POGO occurred when hyperangulated videolaryngoscopy was used to rescue failed Macintosh videolaryngoscopy.…”
Section: Discussionsupporting
confidence: 77%
“…Hyperangulated videolaryngoscopes are designed to improve glottic view beyond that achieved by devices with less pronounced angulation and may perform better in situations where the glottic view would be restricted severely with Macintosh videolaryngoscopes [10]. A subgroup analysis of a recent Cochrane review reported that hyperangulated videolaryngoscopes were more likely to reduce the incidence of failed tracheal intubation when used in patients with known or predicted difficult airways [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation